Markmyprofessor: the More the Better? - Kiss, Marietta; Sátor, Viktor Bence; Kontor, Enikő; Kun, András István (International Journal of Engineering and Management Sciences, 2017)
Student evaluation of faculty members is a current topic both internationally and in Hungary, partly due to the massification and partly due to the marketization of higher education. One of the evaluation methods is the internet-based voluntary rating which was started by ratemyprofessors.com in the U.S.A. and whose Hungarian counterpart is markmyprofessor.com. Research studies on the U.S. website – among many other critics – established that reliability of this evaluation method highly depends on the frequency of ratings: if an individual tutor is evaluated by more students, then the standard deviation of the ratings is smaller. The previous conclusion about the U.S. website is tested in our study based on Hungarian data. Our main result is that many of the experiences about markmyprofessor.com echo the previous findings about ratemyprofessors.com. Beside this in the Hungarian sample the higher response rate is associated with lower average ratings.